A Cognitive Neuroscience View of Voice-Processing Abnormalities in Schizophrenia: A Window into Auditory Verbal Hallucinations?. Issue 2 (March 2016) - Conde, Tatiana; Gonçalves, Oscar F.; Pinheiro, Ana P.
Abstract : Abstract: Auditory verbal hallucinations (AVH) are a core symptom of schizophrenia. Like "real" voices, AVH carry a rich amount of linguistic and paralinguistic cues that convey not only speech, but also affect and identity, information. Disturbed processing of voice identity, affective, and speech information has been reported in patients with schizophrenia. More recent evidence has suggested a link between voice-processing abnormalities and specific clinical symptoms of schizophrenia, especially AVH. It is still not well understood, however, to what extent these dimensions are impaired and how abnormalities in these processes might contribute to AVH. In this review, we consider behavioral, neuroimaging, and electrophysiological data to investigate the speech, identity, and affective dimensions of voice processing in schizophrenia, and we discuss how abnormalities in these processes might help to elucidate the mechanisms underlying specific phenomenological features of AVH. Schizophrenia patients exhibit behavioral and neural disturbances in the three dimensions of voice processing. Evidence suggesting a role of dysfunctional voice processing in AVH seems to be stronger for the identity and speech dimensions than for the affective domain. Abstract : Supplemental digital content is available in the text.